Las empresas de información y documentación en la ingeniería civil - Cendrero Agenjo, Benjamín (Revista General de Información y Documentación, 2007)
The civil engineering companies in the development of their activity need information and documentation about the future customers and about the works to make. This information applies a previous study, because there is a lot of institutions which need the works of the civil engineering companies. Why can not have information and documentation companies making this?